POINT OF VIEW MATEMATIKAWAN TERHADAP PERANAN TENAGA PENDIDIK BIMBINGAN DAN KONSELING DI SEKOLAH - Galeh Febrian Agustino (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2024)
Education is an aspect that has an important role which is carried out consciously by an individual with the aim of improving the individual's quality and abilities in learning. In this case, the way to improve students' quality and abilities in learning is done through guidance and counseling both individually and in groups. Apart from that, in order to improve students' disciplinary character, the role of guidance and counseling teachers in schools is needed. However, from another perspective, it turns out that there are still many who doubt the existence of guidance and counseling teachers, one of which is mathematics teachers. The purpose of writing this article is to find out the importance of the role of guidance and counseling teachers and also the perspective of mathematicians regarding the performance of guidance and counseling teachers in schools. The method used in writing this scientific article is a literature view from books, journals, theses and scientific articles by citing some information related to the role of guidance and counseling teachers and the perspective of mathematics teachers on the performance of guidance and counseling teachers.